Functional State of Local Immune Status in the Inflammatory Process in the Upper Respiratory Tract in Patients Infected With Covid-19 (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In the period from 2020-2021, we examined 53 patients infected with COVID-19 who applied to the infectious diseases department of the Bukhara Regional Infectious Diseases Medical Center. Of these, 32 people suffered from acute rhinosinusitis and 21 people from acute purulent tonsillitis.All patients underwent a standard examination: clarification of complaints and anamnestic data. Examination of the ENT organs was carried out according to the generally accepted scheme. We also studied the indices of local immunity of the mucous membranes of the middle ear using immunohistochemical studies with antibodies to T-helper lymphocytes (CD4 +), suppressor T-lymphocytes (CD8 +) and B-lymphocytes (CD20) in patients of different groups. the indices of local immunity of the mucous membrane of the middle ear in the first two weeks of the acute purulent otitis media correspond to an adequate response of local immunity to an infectious agent; the third week is characterized by an imbalance in the local immune defense, which indicates a high activity of the inflammatory process, which is a milestone stage in the course of the disease.